(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The technological infrastructure in educational centres in Extremadura has grown considerably since the 1990s. Numerous technological resources have been implemented to help teaching and to improve students’ digital competence. This study has aimed to observe the use of ICT resources by teachers in Extremadura and their perceptions of their application in the classroom before the impact of the COVID-19 pandemic on education. A total of 1953 teachers from Extremadura have participated and a cross-sectional descriptive design with a survey has been used. A questionnaire was designed for data collection and validated by carrying out a series of processes, such as the preparation of a first draft based on a previously applied questionnaire, adaptation and review by the research team, validation by experts and reliability checking. The results have shown differences according to gender, level of teaching performance and teaching experience, in the use of IT resources and training in technology. Likewise, it was found that there is a clear positive correlation between these parameters analysed in the teaching staff of Extremadura. The results obtained are of great value and open up new lines of research to compare the differences in the use, knowledge and perception of teachers’ education in ICT resources.